Chemoselective detection of alkyl halides via an iridium(III) luminescent probe. (December 2018) - Wu, Chun; Liu, Jin-Biao; Li, Guodong; Wong, Suk-Yu; Han, Quan-Bin; Leung, Chung-Hang; Ma, Dik-Lung
Abstract: The high reactivity of alkyl halides towards nucleophiles renders them as acutely toxic and mutagenic agents. Therefore, it is urgent to develop simple, sensitive, and selective methods for the detection of alkylating agents in a wide range of scenarios. Herein, we have designed and synthesized a novel cyclometalated iridium(III) complex Ir_1 as a rapid and effective chemosensor for a range of alkyl halides based on cycloaddition reaction. Ir_1 displayed an enhanced luminescence with the increase of BnBr-thiourea concentration, within a linear range of 0.8–8 μM BnBr-thiourea, and the detection limit at a signal-to-noise ratio of 3 was as low as 0.39 μM. Graphical abstract: Image 1 Highlights: An iridium(III) complex probe Ir_1 for alkyl halide detection has been synthesized. Ir_1 underwent a cycloaddition reaction with S -benzylthiouronium. Ir_1 showed high selectivity for alkyl halides.